Research and Analysis of Active Purification and Fragrance Systems for In-vehicle Environment - Zuo Xinyu; Yao Qian; Li Chuanjie; Zhao Yunxia; Hu Junyan; Li Lixuan; Wang Chong; Wu Jinna (E3S Web of Conferences)
With the intensification of volatile organic compounds (VOCs), fine particulate matter (PM2.5), and microbial pollution in passenger vehicles, indoor air quality has become a crucial factor affecting the health and experience of drivers and passengers. This study reveals the interactive mechanism between technological performance and user experience through a comparative analysis of the synergistic effects of active air purification technologies and in-car fragrance systems, combined with empirical research on 17 automotive companies. The research indicates that mainstream automakers are optimizing purification efficiency and fragrance release strategies to meet consumers’ dual demands for health protection and sensory comfort. This article provides a theoretical framework and practical guidance for the iteration and market application of related technologies in the automotive industry.